2015
DOI: 10.1021/ja512746q
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Conjugate Additions of α-Amino Radicals via Cooperative Photoredox and Lewis Acid Catalysis

Abstract: We report the highly enantioselective addition of photogenerated α-amino radicals to Michael acceptors. This method features a dual-catalyst protocol that combines transition metal photoredox catalysis with chiral Lewis acid catalysis. The combination of these two powerful modes of catalysis provides an effective, general strategy to generate and control the reactivity of photogenerated reactive intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
122
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(130 citation statements)
references
References 46 publications
3
122
0
5
Order By: Relevance
“…Elegant work from the Yoon and Melchiorre groups has subsequently demonstrated that by using a chiral Lewis acid or organocatalyst respectively, these transformations can be rendered asymmetric (vide infra). 33,34 …”
Section: Redox-neutral Amine α-Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Elegant work from the Yoon and Melchiorre groups has subsequently demonstrated that by using a chiral Lewis acid or organocatalyst respectively, these transformations can be rendered asymmetric (vide infra). 33,34 …”
Section: Redox-neutral Amine α-Functionalizationmentioning
confidence: 99%
“…149 Of particular note is a report by Yoon and co-workers demonstrating that conjugate additions of α-amino radicals can be rendered asymmetric through the use of a chiral i -BuPyBox-ligated Lewis acid catalyst (Scheme 31a). 33 Here, photoredox catalysis mediates generation of the α-amino radical and the Lewis acid complex controls stereoselectivity in the subsequent addition step. Recently, Meggers and co-workers reported a similar dual photoredox Lewis acid-catalyzed conjugate addition reaction that utilizes organotrifluoroborate salts as the source of the alkyl radical coupling partner (Scheme 31b).…”
Section: Photoredox Lewis Acid Catalysismentioning
confidence: 99%
“…The intermediacy of α-amino radicals to elaborate aryl- and heteroaryl substructures has recently been demonstrated in photoredox catalysis [6,25,28,36] from both unfunctionalized amines (toward the preparation of JAK2 inhibitor LY2784544), [6] and those with the TMS [35,37,38] and CO 2 H [2,39] activating groups (Scheme 1). …”
mentioning
confidence: 99%
“…In somes uch reactions, the resulting electrophilicr adical intermediatesd imerize, rearrange, or cyclize. [12] In others they are able to be reduced to anions by reductive reagents,s uch as the photocatalyst, [13] or low-valent metals [14] to avoid dimerization or polymerization. Reductivep erfluoroalkylation of electron-deficienta lkenesu sing R F Io rR F Br could also be achieved by addition of H-atom donors to reactions initiatedb ya zobisisobutyronitrile( AIBN), Et 3 B/O 2 ,U Vi rradiation, or photocatalysis.…”
mentioning
confidence: 99%